Contribución al estudio del modelado matemático de la fermentación sólida de hongos filamentosos en soportes inertes - Gutiérrez Rojas, Mariano (Universidad Autónoma Metropolitana, 1995)
En el campo de las fermentaciones en medios sólidos (FMS), los soportes inertes se utilizan como medios experimentales ideales en los que se absorben medios de cultivo especificos. En estos medios ideales, los microorganismos utilizan el agua y los nutrientes que contiene el soporte y colonizan las superficies disponibles para producir metabolitos de interés comercial. La utilización de soportes inertes de forma regular también resulta interesante como un medio ideal para la elaboración de modelos matemáticos. En este trabajo, se desarrolló la formulación, solución y validación de un modelo matemático que: describe el crecimiento de un hongo filamentoso sobre el lecho empacado de un soporte inerte de forma esférica regular. Para la formulación del modelo, se utilizó un enfoque fenomenológico local en un sistema constituido por un medio poroso heterogéneo o soporte inerte que contiene agua y nutrientes en su interior. En la superficie de este medio poroso los microorganismos crdcen intercambiando materia con la fase líquida del interior del soporte y, con la fase gaseosa continua que los rodea. Con base en un conjunto de hipótesis, se desarrolló un modelo general constituido por seis variables de estado: (i) biomasa, (ii) azúcares solubles, (iii) agua, (iv) oxígeno, (v) bióxido de carbono, y (vi) temperatura del medio. El comportamiento de cada variable de estado, en el tiempo y en el espacio, se obtiene a partir de los balances de masa, los balances de energía interna y las relaciones cinéticas correspondientes. El modelo general quedó constituido por: (i) seis ecuaciones diferenciales parciales, seis condiciones iniciales y cinco condiciones frontera, (ii) 13 ecuaciones algebraicas asociadas a los balances y las relaciones cinéticas y, (iii) 43 parámetros que incluyen constantes fisicas, biológicas y las condiciones de operación particulares. de sustrato son los siguientes: (i) los rendimientos base producción de biomasa (Yi), (ii) el coeficiente de mantenimiento (m,), (iii) el coeficiente de afinidad por el sustrato (&) y, (iv) el coeficiente de mhbición por el sustrato (IC,). Se demostró que estos parámetros biológicos, no podían considerarse constantes y que debían cambiar con el tiempo de fermentación, i.e. con respe,cto a alguna variable de estado como los azúcares en el medio. También se demostró que, para ajustar satisfactoriamente los resultados experimentales, sería necesario incorporar diferentes valores en los parámetros cinkticos, tanto para el caso del crecimiento, como para el consumo de los azúcares, particularmente los parámetros K, y m,. Por lo tanto, al tratar de ajustar los resultados del modelo, se encontró que el problema tenía múltiples soluciones. Para resolver este problema se utilizó una función que permitió asociar los rendimientos de biomasa Yi con los azúcares del medio. Esta función permitió emplear valores constantes de los tres parámetros IC,, aC, y m, con ajustes satisfactorios a los resultados experimentales. Prácticamente en todos los casos en los que se trató de validar el modelo con altas concentraciones iniciales de azúcares se observó, que se requiere incluir en el modelo al menos un término de formación de producto que justifique el crecimiento celular con el consumo de azúcares, el consumo de oxígeno, y la producción de bióxido de carbono y calor metabólico. El modelo simplificado que se propone, es un simulador flexible de rápida respuesta, con un aceptable grado de fidelidad con los resultados experimentales. Es un modelo que puede contribuir: (i) a la explicación de aspectos físicos y fisiológicos del fenómeno global estudiado, (ii) al desarrollo de las estrategias de operación de biorreactores para otros cultivos en FMS. (iii) a establecer bases para el diseño, control y escalamiento de biorreactores y, (iv) al desarrollo de nuevos modelos más complejos, como es el caso de modelos que consideren los aspectos difusivos de los nutrientes y de los productos.; In the solid state fermentation (SSF) field, inert supports are ideal experimental media in whxh specific culture media can be absorbed. In these ideal media, the microorganisms use the water and nutrients contained inside the support and colonize available surfaces producing commercial metabolites. Inert supports in a regular shape presentation are also particularly interesting as an ideal media in developing mathematical models. In ths work a mathematical model dealing with the growth of filamentous fungi on a packed bed of regular spherical shape inert support is developed, solved, and verified. To develop the model, a local phenomenological approach for a system constituted by a porous heterogeneous medium or inert support containing water and nutrients is considered. Cell growth takes place on the surface of porous medium and microorganisms exchange mass with liquid phase, within the support, and with the surrounding continuos gaseous phase. The general model deals with six state-variables: (i) biomass, (ii) sugar, (iii) water, (iv) oxygen, (iv) carbon dioxide, and (v) medium temperature; a set of hypotheses was taken account. The dynamic and spatial behavior of each state variable is derived from correspondent kinetics and mass and energy balances. The proposed general model involves: (i) six partial differential equations, six initial, and five boundary conditions, (ii) 13 kinetic and balances associated algebraic equations, and (iii) 43 parameters including physical and biological constants and the particular operation conditions. In order to solve such a general model, two complexity levels were approached: 1. In the first level, the general model was simplified to an only time-dependent model. This simplification reduced the model to (i) six ordinary differential equation and six initial conditions, (ii) 13 algebraic equations, and (iii) 36 parameters. All parameters were estimated as a function of the physical characteristics of each constituent, the particular operation conditions, and a stoichiometrical reaction which transforms sugars into biomass. The model, in a cylindrd coordinate system, and in a normalized form was solved by using the fourth order Runge-Kutta numerical integration algorithm. 2. 'In the second level, the general model was retained as time and space-dependent. In this level, same values for parameters found in the simplified model were used and for the rest of parameters new values were searched. The model, in a cylindrical coordinate system, and in a normalized form was solved by using the finite differences method, in which an explicit in time, explicit in the axial ordinate, and implicit in the radial ordinate strategy was used. Qualitative and quantitative results, in all of the two approaches, showed a good agreement with the physical and biological principles that encouraged the model. To validate and fit results the simplified model was used. Model predictions were compared to experimental results obtained under different operation conditions (increasing initial sugar concentrations were also included) by using small packed bed reactors at laboratory scale. It was found that sugar consumption and cell growth were clearly influenced by the following parameters (i) the biomass yields (Yi), (ii) the maintenance coefficient (m,), (iii) the affinity substrate cefficient (&), and (iv) the inhibition constant (K,). It was shown that these biological parameters could not be considered as a constants but variables as a function of fermentation time, Le. as a function of any state variable such as sugar in the medium. In order to fit experimental satisfactorily, it was shown that should be necessary to include different values for the kinetic parameters to fit cell growth and different values to fit sugar consumption, particularly in the cases of K, and q. Therefore, when trying to fit results always a multiple solutions problem was emerged. To solve such a problem the yields Yi, were explicited as a function of sugar in the medium. The introduction of the Yi function in the model allowed to keep constant values for the rest of biological parameters producing satisfactory fittings. In order to justify simulated cell growth patterns with, sugar and oxygen consumption, carbon dioxide, and metabolic heat evolution, it was shown, practically in all assayed cases in whch high initial sugar concentration was used, that a product formation term is required in the model. The proposed simplified model can be regarded as a flexible quick-response simulator with an acceptable accuracy to experimental data. Furthermore, the model could be a helpful simulation tool in: (i) explaining physical and physiological aspects involved in the studied phenomenon, (ii) developing the suitable bioreactor operating strategies for any other SSF culture, (iii) Setting up bases to the design, control and scale-up of bioreactors, and (iv) developing more complex models such as diffusive models.